Functional characterisation of type III secretion system effector protein, BIPC, in Burkholderia pseudomallei pathogenesis / Kang Wen Tyng - Kang , Wen Tyng (2017)
Burkholderia pseudomallei, a facultative intracellular pathogen, possesses virulence determinants, that allow the bacterium to both invade the host and evade the host immune response, thereby initiating an infection progressing to a fulminating disease. Some of these virulence determinants are known to be coded by the bsa locus of B. pseudomallei. This bsa locus encodes several proteins which are components of the type III secretion system (TTSS) required for the pathogen to deliver virulence factors directly into the cytoplasm of the host cells. Interestingly, although the B. pseudomallei genome encodes three predicted TTSSs clusters (i.e. TTSS-1, TTSS-2, and TTSS-3), only the TTSS-3 is important for bacterial pathogenesis and plays a vital role in the intracellular lifecycle of this pathogen. BipC was postulated as one of the TTSS-3 effector proteins, but its role in the pathogenesis of B. pseudomallei infection is not well understood. Thus, in this study, attempts were made to dissect the functional role of BipC in virulence using in vitro and in vivo infection models, microarray, and protein analyses. A TTSS-3 deficient strain of B. pseudomallei bipC was generated using an insertion inactivation technique and a complementation strain was also constructed. Phenotypic characterisations of these strains were performed both under in vitro and in vivo conditions. Phagocytic (U937) and non-phagocytic (A549 and HeLa) cells were utilised in in vitro assays. Results showed a significant 2-fold reduction in the percentage of adherence, invasion, and intracellular survival of the bipC mutant compared to the wild type and complemented strains. In addition, the capacity of bipC mutant to spread from cell to cell was severely impaired with a defect in its actin-based intracellular motility. The complemented strain demonstrated a success in restoration to the wild type in all the assays that were performed confirming the role of BipC. These significant iv attenuations for the phenotypic assays were solely due to the inactivation of bipC. Moreover, the virulence of the mutant strain in a murine model for melioidosis using the BALB/c mice was also determined and the results demonstrated that the mutant was less virulent than the wild type. Taken together, these results suggest that BipC might play a crucial role in the infectious cycle of the pathogen by facilitating entry into and exit from the host cell. Microarray analysis was performed in order to further understand the mechanisms of host defence and host-pathogen dialogue involving the BipC protein in B. pseudomallei pathogenesis. The expression profile was generated for liver and spleen samples of mice infected with wild type or mutant strains and it was found that a total of approximately 1000 genes were transcriptionally affected by the bipC deletion. Furthermore, the analysis demonstrated that pathways, such as bacterial invasion of epithelial cells, regulation of actin cytoskeleton, MAPK signalling pathway, and p53 signalling pathway may be regulated by BipC in vivo. These results suggest that BipC mainly targets pathways related to cellular processes and these were transcriptionally altered throughout the course of the host response to B. pseudomallei. Proteomics study of the BipC protein was performed to ascertain the exact roles of this protein and how it fulfils its various indicated functions. BipC was verified to subvert the host actin dynamics as demonstrated in vitro by the capability to polymerise actin which promotes cell invasion. Collectively, the novel description of actin nucleation induced by BipC suggests that this protein could modulate the cellular trafficking processes which provide crucial insights into the unique intracellular lifecycle of B. pseudomallei.